Financial literacy and financial crime: A regression discontinuity approach - Freed, Paul G.; Hackney, John (Journal of Financial Economics, 2026)
This study investigates how financial literacy shapes the propensity of individuals to commit financial crime. Using state-level administrative data on criminal charges linked to comprehensive public records , we exploit a policy-based discontinuity in grade level assignment based on individual birth dates that exogenously requires certain high school cohorts to attend a financial literacy course. Our estimates suggest that exposure to the course reduces the propensity to commit financial crime by 37%. The reduction is driven by declines in embezzlement and is stronger for low-income individuals. Additional evidence suggests that the reductions are primarily explained by improvements in household balance sheets.